Research of the optimal variable defects of the preventive maintenance of medicinal equipment - Pongrac, Dalibor (Array, 2019)
The article clarifies the importance of maintenance in the exploitation of a particular medical device from the aspect of maintaining its availability, reliability and overall functionality. Particularly emphasized is the role of the preventive method or procedures that have a preventive character before the problems arise in the work. Through an analysis of the most common malfunctions and causes that occur during the exploitation, a basis for objective defining and proposing principles has been created – preventive maintenance with special emphasis on preventive maintenance according to an established condition. The article also shows a numerical way of calculating the periodicity of conducting preventive examinations on a particular device.